Business Angels and Firm Performance: First Evidence from Population Data - Fredrik W. Andersson; Magnus Lodefalk (Örebro University School of Business, 2020)
Business angels dominate early-stage investment in firms, but research on their investment effects is scarce and is limited by sample selection. Therefore, we propose an algorithm for identifying business angel investments from total population data. We apply the algorithm to study business angels' effects on firm performance, using detailed and longitudinal total population data for individuals and firms in Sweden. Employing these data and a quasi-experimental estimator, we find that business angels invest in firms that already perform above par. There is also a positive effect on subsequent growth compared with control firms. Firms with business angel investments perform better in terms of sales growth, employment growth and the likelihood of becoming a high-growth firm. However, contrary to previous research, we cannot find any impact on firm survival. Overall, our results underline the need to address sample selection issues both in identifying business angels and in evaluating their effects on firm performance.
Keywords: C23; G24; G32; L25; 330; business angels; firm performance; sample selection; population data